The anti-fatigue action of cocaine and habituation to coca in Peru - Cabieses Molina, Fernando (1946)
The concept of fatigue, stressing that this is a likely to be broken down into a series of links, the main process is first established in broad terms: fatigue of central synapses, fatigue neuromuscular plate and fatigue of the muscle fiber. The central synapses fatigue related to movement, is explained by the breakdown of some of the chemical equilibrium states that characterize the function of the neuron. It is located in the synapse and its essence is the inability to transmit nerve impulses through the various neural links. In outline, this is a failure of chemical intermediates for acquiring needed to transmit the impulse, or an inability of the neuron to be excited by a normal concentration of intermediate concentration. Lowering the threshold of neurons produce theoretically decreasing fatigue. Mental fatigue, behaves apparently suigiendo the same general rules. In the neuromuscular junction, prolonged maintenance jobs also involve a series of metabolic steady states, the main the acetylcholine metabolism. Also play an important role ions. Fatigue of the muscle fiber, presupposes the existence of large metabolic imbalances that never occur in the normal organism, prevent fatigue CNS and neuromuscular plate. The metabolic processes involved in muscle contraction, nevertheless play a key role in the development of the total fatoga produced by an inability of the systems metabolic recovery to pay debts contracted by muscles. The various stages of fatigue are closely related in the normal body, depending on each other mutually.